Political upheaval in Sri Lanka: Internal and external consequences of the parliamentary elections on 5 August 2020 - Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2020)
The results of the 16th parliamentary elections in Sri Lanka mark a political upheaval in several respects. First, Sri Lanka Podujana Peramuna (SLPP), founded in 2016, and its allies now have a two-thirds majority in parliament. Prime Minister Mahinda Rajapaksa and his brother President Gotabaya Rajapaksa therefore have a free hand to push through a new constitution. This will strengthen their power and the privileges of the Buddhist majority. Second, the poor performance of established parties - such as the United National Party (UNP) and the Sri Lanka Freedom Party (SLFP), which have shaped political developments since independence in 1948 - seems to indicate a change among the elites. Third, the fragmentation of the Tamil parties weakens their recurring demand for greater regional autonomy. If the Rajapaksa brothers return to an authoritarian course, as they did during Mahinda's last term of office, which ended in 2015, political polarisation will increase again, both within the Sinhala majority and among the minorities.
Keywords: 320